2015
DOI: 10.1016/j.sbspro.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

The Factors that Influence the Transfer of Training in Disaster Preparedness Training: A Review

Abstract: Every organisation and government invests in implementing effective training programmes to maximize the inherent value of their existing human capital. Human development training programmes have been an integral part in encouraging the employees to be a competent and skilled labour force that is knowledgeable and able to perform assigned tasks. Disaster preparedness training is one of training programmes provided to employees and volunteers to prepare and reduce the effects of a disaster such as flood. A varie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
2
4
0
Order By: Relevance
“…Practical-oriented and experience-based training was described as the preferred method of skills training. The results are in line with a previous review on the factors that influence the transfer of training in disaster preparedness training and also a study on barriers to implementation of CPR training, which indicated learners' preference for experience-based learning methods (22,23). The method therefore needs to focus on skill-based training for laypersons because it has been shown to be effective in imparting knowledge and skills and also in boosting participants' self-confidence as they learn to perform new skills (22).…”
Section: Discussionsupporting
confidence: 90%
“…Practical-oriented and experience-based training was described as the preferred method of skills training. The results are in line with a previous review on the factors that influence the transfer of training in disaster preparedness training and also a study on barriers to implementation of CPR training, which indicated learners' preference for experience-based learning methods (22,23). The method therefore needs to focus on skill-based training for laypersons because it has been shown to be effective in imparting knowledge and skills and also in boosting participants' self-confidence as they learn to perform new skills (22).…”
Section: Discussionsupporting
confidence: 90%
“…Practical-oriented and experience-based training was described as the preferred method of skills training. The results are in line with a previous review on the factors that influence the transfer of training in disaster preparedness training and also a study on barriers to implementation of CPR training, which indicated learners' preference for experiencebased learning methods [22,23]. The method therefore needs to focus on skill-based training for laypersons because it has been shown to be effective in imparting knowledge and skills and also in boosting participants' self-confidence as they learn to perform new skills [22].…”
Section: Discussionsupporting
confidence: 87%
“…A tabletop exercise is a training approach aimed at improving nurses' competencies in this regard [8]. A tabletop exercise is a simulation exercise used for training responses to disasters and emergency situations [9] and has been proposed as an effective method for preparing for large-scale bioterror attacks and pandemics [10]. Tabletop exercise participants were instructed to discuss and create realistic and practical response plans according to the characteristics of their own healthcare institution and based on scenarios similar to the settings they are likely to encounter during a real-life outbreak of an infectious disease [11].…”
Section: Introduction 1rationale Of the Researchmentioning
confidence: 99%